FAKTOR YANG MEMENGARUHI KEBIJAKAN DIVIDEN PERUSAHAAN MANUFAKTUR DENGAN FIRM SIZE SEBAGAI MODERASI - Sherine, Sherine; Setijaningsih, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2024)
This research aims to analyze the effect of sales growth, leverage, and liquidity with firm size as a moderating variable in manufacturing companies listed on Indonesia Stock Exchange during 2017-2020. The sample was selected by purposive sampling method and the valid data were 100 samples. The data processing technique uses the Eviews 12 and Microsoft Excel 2019. The result of this research indicate that sales growth and liquidity have no effect on dividend policy, leverage has negative effect on dividend policy, firm size does not moderate the effect of sales growth and liquidity on dividend policy. This study also indicates that firm size moderate the effect of leverage on dividend policy.